O OBSCURO E A LUZ: “O PAPEL DE PAREDE AMARELO” DE CHARLOTTE PERKINS GILMAN - The darkness and the light: “The yellow Wallpaper” from Charlotte Perkins Gilman (NOVO SITE: https://periodicos.upe.br/index.php/revdia, 2017)
Resumo: O artigo visa perceber a indubitabilidade entre o insólito e a razão em “O papel de parede amarelo” (1892) de Gilman e o analisar à luz dos estudos sobre a loucura de Foucault (1926-1984). Charlotte Perkins Gilman em decorrência do agravamento de seu quadro depressivo ao descobrir um câncer de mama se suicidou em 1935. Charlotte Perkins Gilman (1860- 1935) had claimed for women’s right, being involved in feminist militancy groups. She was a writer of novels and short tales, and she suffered of depression her whole life. In her fantastic tale “The yellow paper” (1892) she could had seen a chance to exorcise her fears, dreads and anguish through her characters by putting them to the edge of a collapse. The article mains realize the indubitability between the uncommon and the reason in Gilman’s short tale “The yellow paper”. Besides, we main to analyze the horror’s short tale by basing it on the insanity’s studies of Foucault (1926-1984). Charlotte Perkins Gilman had her depression aggravated in consequence of a breast cancer and killed herself in 1935.